2012
DOI: 10.1017/s0007114512001717
|View full text |Cite
|
Sign up to set email alerts
|

A randomised study on the effects of fish protein supplement on glucose tolerance, lipids and body composition in overweight adults

Abstract: The popularity of high-protein diets for weight reduction is immense. However, the potential benefits from altering the source of dietary protein rather than the amount is scarcely investigated. In the present study, we examined the effects of fish protein supplement on glucose and lipid metabolism in overweight adults. A total of thirty-four overweight adults were randomised to 8 weeks' supplementation with fish protein or placebo tablets (controls). The intake of fish protein supplement was 3 g/d for the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
79
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 36 publications
(47 reference statements)
10
79
4
Order By: Relevance
“…This is supported by results from animal studies showing that fish proteins may have a lowering effect on TAG and cholesterol as well as improve glucose tolerance (19)(20)(21)(22)(23)(24)(25)(26) . In line with this, we have recently shown that supplementation with cod protein as tablets reduced fasting glucose and LDL-cholesterol as well as postprandial glucose concentrations in healthy, overweight adults (17) . The present study was designed to investigate the impacts of high intake of lean or fatty fish (cod and salmon, respectively) compared with lean meat (chicken) on indicators of CVD and type 2 diabetes risk factors, including lipid and glucose regulation.…”
supporting
confidence: 60%
See 4 more Smart Citations
“…This is supported by results from animal studies showing that fish proteins may have a lowering effect on TAG and cholesterol as well as improve glucose tolerance (19)(20)(21)(22)(23)(24)(25)(26) . In line with this, we have recently shown that supplementation with cod protein as tablets reduced fasting glucose and LDL-cholesterol as well as postprandial glucose concentrations in healthy, overweight adults (17) . The present study was designed to investigate the impacts of high intake of lean or fatty fish (cod and salmon, respectively) compared with lean meat (chicken) on indicators of CVD and type 2 diabetes risk factors, including lipid and glucose regulation.…”
supporting
confidence: 60%
“…It should be noted that as all participants had serum lipid concentrations within the normal reference ranges the clinical significance of the effects of fatty fish intake on TAG and HDL-cholesterol concentrations in serum is uncertain. We have recently shown that cod protein supplementation reduced serum LDL-cholesterol concentration in overweight adults, with no effect on serum concentrations of TAG, total cholesterol and HDL-cholesterol (17) . Reduced serum TAG has been reported in overweight subjects when lean fish was part of …”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations